Influence of Covid-19 Pandemic on the Economy of Tokumbo Vehicles Trade in Borno State: Implications for Counselling - Ibrahim Dahiru Idriss; Ngohi Bukar Umar (International Journal of Emerging Issues in Islamic Studies, 2021)
Abstract The study was an opinion survey that investigated the influence of covid-19 pandemic on the economy of Tokumbo vehicles trade in Borno State, Nigeria. Population of the study comprised of all fairly used secondhand car dealers in the State. However, 150 Tokumbo car dealers constituted the sample. Purposive and stratified random sampling techniques were used in selecting sample. Researchers designed 18 items Structured Interview Schedule (SIS) tagged “Car Dealers Interview Schedule (CDIS)” and Focus Group Discussion (FGD) were the instruments used to elicit data for the study. The CDIS was divided into two parts (A & B). Part A collected information on demographic characteristics of the respondents while Part B elicited data on sources of capital for the Tokumbo dealers, brand of Tokumbo vehicles and the influence of covid-19 pandemic on Tokumbo trade in Borno State, Nigeria. The CDIS was validated by three experts in the field of Business Administration of the University of Maiduguri, Borno State and a coefficient of 0.74 was obtained using Cronbach alpha reliability method for the internal consistency which was considered relevant and adequate for the study. Descriptive statistics of frequency counts, percentage and bar graph were used in analyzing data collected for the study. Three objectives and three research questions piloted the study. Results of the study revealed loan and personal savings as some of the sources of capital for dealers in Tokumbo vehicles in Borno State. Toyota, Volkswagen, Honda, Mercedes Benz and Peugeot were some of the brands of Tokumbo cars in the study area while rent, loan repayment and gross reduction in sales were some of the effects of covid-19 pandemic on the trade in Tokumbo vehicles in Borno State, Nigeria. Based on the findings, implications for counselling, conclusions and recommendations were made.